Pengaruh Konsep Neitzhe Terhadap Inovasi Teknologi - Habib Suprayoga (Jurnal SIGMA, 2024)
This article explores the influence of Friedrich Nietzsche's philosophical concepts, namely the will to power, Übermensch, and eternal recurrence, on technological innovation, the ethics of technology use, and sustainability. Using an interdisciplinary approach, this research examines how Nietzsche's views can offer new perspectives for a technology-based future, emphasizing the importance of ethics in technology development and sustainabilityKeywords: Will to Power, Übermensch, Eternal Recurrence, Technological Innovation, Ethical Use, Sustainability, Friedrich Nietzsche